2018
DOI: 10.21608/jppp.2018.43750
|View full text |Cite
|
Sign up to set email alerts
|

Biological Performance, Development and Life Table of Bird Cherry-Oat Aphid Rhopalosiphum padi (L) (Hemiptera: Aphididae) on some Egyptian Wheat Cultivars

Abstract: The bird Cherry-oat aphid Rhopalosiphum padi (L) causes serious damage in cereal producing countries including Egypt. The biological performance and development of R. padi on ten Egyptian wheat cultivars including

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…The percentage of nymphal survival varied from highest on Beni Suef 5 (96.1%) to lowest on Sids 12 (86.3%). These results in agreement with Taheri et al (2010) and Aly (2018) who found that the developmental time and mortality of nymphal stage of aphids indicated significant differences among the examined wheat varieties. The values are presented as means ± SE of ten replicates.…”
Section: Development and Fecundity (No-choose): 1developmental Time And Survivorship Of Nymphssupporting
confidence: 92%
“…The percentage of nymphal survival varied from highest on Beni Suef 5 (96.1%) to lowest on Sids 12 (86.3%). These results in agreement with Taheri et al (2010) and Aly (2018) who found that the developmental time and mortality of nymphal stage of aphids indicated significant differences among the examined wheat varieties. The values are presented as means ± SE of ten replicates.…”
Section: Development and Fecundity (No-choose): 1developmental Time And Survivorship Of Nymphssupporting
confidence: 92%